A cancer-associated TP53 synonymous mutation induces synthesis of the p53 isoform p53/47 - Sajwan, Rhythm; Wang, Lixiao; Casar-Borota, Olivera; Karakostis, Konstantinos; Chen, Sa; Fahraeus, Robin; Gu, Xiaolian; Vadivel Gnanasundram, Sivakumar (British journal of cancer, 2025)
BACKGROUND: Synonymous mutations (SMs) change the mRNA nucleotide sequences without altering the corresponding amino acid sequence and are usually overlooked due to their perceived lack of influence on protein function. However, emerging reports suggest that SMs play a significant role in disease development and progression. METHODS: Whole exome sequencing, RNA-sequencing, and droplet digital PCR were performed to identify the SMs from the malignant glioma patients. MutaRNA was used to predict the effect of SMs on RNA structure in silico. SHAPE-MaP was performed to probe and assess the effect of SMs on RNA structure in-cellulo. RESULTS: Here, we report that a Cancer-Associated SM in TP53 codon valine 203 (CASM203) results in the induction of the alternative translation initiated p53 protein isoform, p47. In-cell high-throughput RNA structural mapping showed that CASM203 mimics the Protein Kinase RNA-Like ER Kinase (PERK)-mediated p53 mRNA secondary structure that induces p47 expression of during the unfolded protein response (UPR). CONCLUSIONS: Overall, the single gain-of-function SM mimics the UPR-mediated p53 stress response, by generating RNA secondary structures akin to the PERK-mediated p53 mRNA structural switch. This illustrates the link between RNA structures and cellular biology and underscores the importance of SMs in cancer biology and their potential to further refine genetic diagnostics.
Keywords: Tumor Suppressor Protein p53; Unfolded Protein Response; sekvenování exomu; Humans; Exome Sequencing; gliom; RNA, Messenger; Cell Line, Tumor; signální dráha UPR; nádorové buněčné linie; protein - isoformy; Silent Mutation; Brain Neoplasms; tichá mutace; nádory mozku; lidé; Glioma; messenger RNA; nádorový supresorový protein p53; Protein Isoforms